Colombian agriculture, “peasant’s life project” to avoid migration to big cities - Pinzón Herrera, Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
From the analysis and documentary review, a descriptive cause-effect study of peasant migration to large cities is generated, in order to identify the genesis of the problem and propose strategies that allow the strengthening of agricultural activity based on policies that guarantee use, property and legality of rural territories in Colombia, seeking to professionalize the field as a setting for multiple opportunities for current and future generations, a field capable of generating wealth, preserving, prolonging and renewing an agricultural culture that creates sufficient resources to satisfy needs and achieve personal, professional and economic of the peasant communities.